Nano-MoO3-mediated synthesis of bioactive thiazolidin-4-ones acting as anti-bacterial agents and their mode-of-action analysis using in silico target prediction, docking and similarity searching. (7th January 2016) - Kumar, Keerthy Hosadurga; Paricharak, Shardul; Mohan, Chakrabhavi Dhananjaya; Bharathkumar, Hanumantharayappa; Nagabhushana, G. P.; Rajashekar, Dinesh Koragere; Chandrappa, Gujjarahalli Thimmanna; Bender, Andreas; Basappa,; Rangappa, Kanchugarakoppal Subbegowda
Abstract : Thiazolidin-4-ones inhibit bacterial growth by potentially targeting the FtsK motor domain of DNA translocase of Salmonella typhi . Abstract : The efficacy of thiazolidin-4-ones as synthons for diverse biological small molecules has given impetus to anti-bacterial studies. Our work aims to synthesize novel bioactive thiazolidin-4-ones using nano-MoO3 for the first time. The compelling advantage of using nano-MoO3 is that the recovered nano-MoO3 can be reused thrice without considerable loss of its catalytic activity. The synthesized thiazolidin-4-ones were tested for anti-bacterial activity against two strains of pathogenic bacteria, namely, Salmonella typhi and Klebsiella pneumoniae . Our results indicated that 3-(benzo[ d ]isoxazol-3-yl)-2-(3-methoxyphenyl)thiazolidine-4-one (compound3b ) showed significant inhibitory activity towards Salmonella typhi, in comparison with gentamicin. Furthermore, in silico target prediction presented the target of compound3b as the FtsK motor domain of DNA translocase of Salmonella typhi . Hence, our hypothesis is that compound3b may disrupt chromosomal segregation and thereby inhibit the division of Salmonella typhi . In addition, similarity searching showed that 34 compounds with a chemical similarity of 70% or higher to compound3b, which were retrieved from ChEMBL, bound to targets associated with biological processes related to cell development in 36% of the cases. In summary, our work details novel usage of nano-MoO3 for the synthesis of novel thiazolidin-4-ones possessing anti-bacterial activity, and presents a mode-of-action hypothesis.